Improving Learning Outcomes in Solid Geometry through Project-Based Learning (PjBL) Using Concrete Media in Grade 3 at SDN 6 Kaur - Rohani Astariah; Arum Ratnaningsih (Global Education Journal, 2026)
Mathematics learning in elementary schools is essential for developing students’ logical thinking and problem-solving skills. However, learning outcomes in solid geometry often remain low due to abstract teaching methods, limited instructional media, and low student engagement. This study aimed to improve students’ Mathematics learning outcomes on the topic of solid geometry through the implementation of Project-Based Learning (PjBL) using concrete media. The study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 25 third-grade students of SD Negeri 6 Kaur, Bengkulu. Data were collected through achievement tests, observations, and documentation. The results showed improvements in both learning implementation and student achievement. The observation score of PjBL implementation increased from 75% in Cycle I to 91.67% in Cycle II. Students’ average score improved from 65 to 82, while the mastery learning percentage increased from 60% to 90%. In addition, students demonstrated higher levels of participation, collaboration, creativity, and conceptual understanding. These findings indicate that Project-Based Learning (PjBL) supported by concrete media is effective in improving elementary school students’ learning outcomes in solid geometry.